2012
DOI: 10.4315/0362-028x.jfp-11-528
|View full text |Cite
|
Sign up to set email alerts
|

Control of Listeria monocytogenes on Frankfurters and Cooked Pork Chops by Irradiation Combined with Modified Atmosphere Packaging

Abstract: This study was conducted to investigate the efficacy of controlling Listeria monocytogenes on frankfurters and cooked pork chops with irradiation and modified atmosphere packaging (MAP) containing a high concentration of CO2. Frankfurters and cooked pork chops were inoculated with a five-strain cocktail of L. monocytogenes and packaged in vacuum or high-CO2 MAP. Irradiation was applied to each product at 0, 0.5, 1.0, or 1.5 kGy. No significant packaging effect was found for the radiation sensitivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The D 10 value of both bacteria in all produced commodities increased more than two-fold (p < 0.05) compared to the irradiated controls (sealed bags without vacuum). However, this is not always verified, a vacuum treatment can lead to lower D 10 values than an air treatment, probably due to the accumulation of the stresses to which the microorganism is subjected [56]. Sommers and Boyd [28] reported that the modified atmosphere with 100% N 2 , 50% N 2 plus 50% CO 2 , or 100% CO 2 did not affect the radiation resistance of E. coli O157:H7, Salmonella, L. monocytogenes and S. aureus.…”
Section: Extrinsic Factorsmentioning
confidence: 99%
“…The D 10 value of both bacteria in all produced commodities increased more than two-fold (p < 0.05) compared to the irradiated controls (sealed bags without vacuum). However, this is not always verified, a vacuum treatment can lead to lower D 10 values than an air treatment, probably due to the accumulation of the stresses to which the microorganism is subjected [56]. Sommers and Boyd [28] reported that the modified atmosphere with 100% N 2 , 50% N 2 plus 50% CO 2 , or 100% CO 2 did not affect the radiation resistance of E. coli O157:H7, Salmonella, L. monocytogenes and S. aureus.…”
Section: Extrinsic Factorsmentioning
confidence: 99%
“…Electron beam (E‐beam) treatment is considered a process that can ensure that food safety standards are met without significant losses in food quality (Li & Farid, ; Pillai & Shayanfar, ; Roberts, ). Moreover, several authors have described its efficacy in reducing L. monocytogenes in various meat products, such as bologna, frankfurters, cooked pork and turkey ham (Foong, Gonzalez, & Dickson, ; Kudra et al, ), pork and beef loin (García‐Márquez, Cambero, Ordonez, & Cabeza, ; Yim, Jo, Kim, Seo, & Nam, ), duck meat (An et al, ; An, Jo, Akram, Suh, & Kwon, ), fermented sausages (Cabeza et al, ), and dry‐cured and cooked ham slices (Benedito et al, ; Cabeza et al, ; Cabeza et al, ; Cambero et al, ; Hoz, Cambero, Cabeza, Herrero, & Ordonez, ).…”
Section: Introductionmentioning
confidence: 99%